Аналіз умов і механізмів формування вибухонебезпечних сумішей на ранній стадії розвитку Чорнобильської аварії - Азаров, С.І.; Сидоренко, В.Л.; Євланов, В.М.; Гаврилюк, М.М. (Ядерна та радіаційна безпека, 2016)
Розроблено сценарій ранньої стадії розвитку аварії з оцінкою впливу вибухонебезпечного водню на конструкцію реактора РВПК-1000. Показано, що визначальним фактором створення умов вибухонебезпечної водневмісної пароповітряної суміші в активній зоні реактора є співвідношення швидкості локальної генерації газоподібного водню та швидкості поширення водню в парогазовому середовищі активної зони реактора. Разработан сценарий ранней стадии развития аварии с оценкой влияния взрывоопасного водорода на конструкцию реактора РБМК-1000. Показано, что определяющим фактором создания условий взрывоопасной водородсодержащей паровоздушной смеси в активной зоне реактора является соотношение скорости локальной генерации газообразного водорода и скорости распространения водорода в парогазовой среде активной зоны реактора. The paper presents the scenario developed for an early stage of the accident progression to assess impact of highly explosive hydrogen on RBMK-1000 design. It was found out that the ratio between the speed of local generation of gaseous hydrogen and the speed of hydrogen spreading in the vapor-gas medium of the core is the determining factor for the occurrence of conditions of explosive vapor-air mixture in the core. Obtained data can be used in further studies to model the formation of explosive mixtures in the environment, the amount of air and water vapor in the analysis of explosive vapor-air mixture. Practical calculations make it possible to assess fracture energy and predict the impact on structures.